2022
DOI: 10.1021/acsami.2c03183
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Polydopamine Beads: A Photothermally Active Support for Noble Metal Nanocatalysts

Abstract: Polydopamine (PDA) is a unique bioinspired synthetic polymer that integrates broadband light absorption, efficient photothermal transduction, and versatile surface-adhesion functions in a single material entity. Here, we utilize colloidal PDA beads in the submicron particle size regime as an easily processable and photothermally active support for sub-10 nm Pd nanocatalysts to construct a multifunctional material system that allows us to kinetically boost thermal catalytic reactions through visible and near-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…The PDA-supported Pt, Pd, and Rh nanocatalysts exhibited strikingly different behaviors when catalyzing the transfer of hydrogen from the hydrogen donors (FA or AF) to the hydrogen-accepting substrate molecules, MO. Noble metal nanoparticles can catalyze the dehydrogenation of FA and AF to produce CO 2 , ,,, and the hydrogen released from FA and AF can be utilized to chemoselectively hydrogenate the azo bond in MO, which eventually leads to the formation of 4-aminobenzenesulfonate and 4- N , N -dimenthylaminobenzene upon the cleavage of the azo bond ,, (see schematic illustrations in Figure A,B). Therefore, the overall molecule-transforming process is essentially a hydrogenolysis process involving a catalytic transfer hydrogenation reaction further coupled with bond cleavage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PDA-supported Pt, Pd, and Rh nanocatalysts exhibited strikingly different behaviors when catalyzing the transfer of hydrogen from the hydrogen donors (FA or AF) to the hydrogen-accepting substrate molecules, MO. Noble metal nanoparticles can catalyze the dehydrogenation of FA and AF to produce CO 2 , ,,, and the hydrogen released from FA and AF can be utilized to chemoselectively hydrogenate the azo bond in MO, which eventually leads to the formation of 4-aminobenzenesulfonate and 4- N , N -dimenthylaminobenzene upon the cleavage of the azo bond ,, (see schematic illustrations in Figure A,B). Therefore, the overall molecule-transforming process is essentially a hydrogenolysis process involving a catalytic transfer hydrogenation reaction further coupled with bond cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…32 This PDA-mediated colloidal synthesis approach could also be adopted to synthesize PDA-supported nanocatalysts composed of other non-Pt noble metal elements. 33 In this work, we focus on the comparative studies of Pt, Pd, and Rh, which constitute the palladium-group platinum-group (PPG) noble metal family. The three PPG metal elements, which are arranged right next to each other in the periodic table, not only share the same face-centered cubic (fcc) crystalline structure with closely matched lattice parameters but are also expected to exhibit similar chemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient solar harvest is vital for living organisms to survive in harsh environments, and natural pigments such as melanin, which has unique solar-thermal properties play a variety of key roles in the thermoregulation of ectotherms. In recent years, melanin has attracted much interest for its outstanding properties, such as anti-ultraviolet (UV), [40,41] metal chelating, [42] free radical scavenging, [43,44] and thermoregulation. [45,46] PDA, the most common type of synthetic melanin, has been revealed that its physicochemical properties are generally similar to those of natural melanins, thus PDA has been used as photoprotectors, antioxidants, [43] semiconductors, [47] and biomedical materials.…”
Section: The Dark Film For Photothermal Conversionmentioning
confidence: 99%
“…In addition, unlike Pt and other noble metal elements that typically crystallize into the face-centered cubic (fcc) structures, the hexagonal close-packed (hcp) phase of Ru is thermodynamically favored over the fcc phase. , Therefore, Pt and Ru represent a pair of contrasting PGM elements well-worthy of systematic comparative studies. We chose colloidal PDA particles as a structurally stable and catalytically inert support material , for Pt and Ru nanocatalysts, whose sizes were both carefully tuned to ∼2.3 nm. The unique surface-adhesion function of PDA enables us to deposit PGM nanoparticles with finely tunable sizes, narrow size distributions, and ligand-free clean surfaces onto the PDA supports through a one-pot PDA-mediated metal deposition process. , Selecting ligand-free Pt and Ru nanoparticles of essentially the same sizes dispersed on the same support material as the model catalysts for detailed kinetic and mechanistic studies enables us to unambiguously decipher the intrinsic composition-dependence of catalytic behaviors without further complications caused by inconsistency in particle sizes, support materials, or surface-capping molecular ligands.…”
Section: Introductionmentioning
confidence: 99%